NECK CIRCUMFERENCE AS AN ADIPOSITY INDICATOR AND PREDICTOR OF CARDIOMETABOLIC RISK IN ADOLESCENTS - Pereira, Patrícia Feliciano; Miranda, Valter Paulo Neves; Rocha, Naruna Pereira; Hermsdorff, Helen Hermana Miranda; Peluzio, Maria do Carmo Gouveia; Fraceschini, Sylvia do Carmo Castro; Priore, Silvia Eloiza (ARACÊ, 2025)
Objective: To investigate the association between neck circumference (NC) with the central and total adiposity, as well as cardiometabolic risk factors in adolescents. Design: A sectional study included 476 students (53% boys) from 10 to 19 years old of Brazilian population. Weight, height, neck and waist circumferences were measured following standard protocols and total body fat, trunk and android fat were obtained by dual-energy X-ray absorptiometry. Glicidic and lipidic profile, uric acid and arterial pressure have been assessed, and life style characteristics were self-reported. The adolescents were classified according to the presence of insulin resistance (IR) and metabolic syndrome (MetS). Results: The NC presented positive association with total fat body, trunk and android (p